FEATURES OF LOGO DESIGN DEVELOPMENT WITH ETHNIC AND ETHNO-NATIONAL ELEMENTS - Noha, Anastasiia; Vasylieva, Olena; Shaura, Alina; Padun, Volodymyr (Theory and practice of design, 2025)
Purpose. To explore the aesthetic principles underlying the formation of brand identity based on ethno-design in the contemporary Ukrainian visual environment. To identify how ethnic symbolism – including ornaments, colors, archetypal forms, and typographic stylizations – is integrated into the logos of Ukrainian brands and state institutions. Methodology. To achieve the stated objective, a visual-analytical method, elements of semiotic and content analysis, as well as comparative analysis, were applied. The study focused on over 100 logos of Ukrainian brands and institutions across various fields – culture, education, commerce, and government administration. All objects were selected for the presence of ethnic elements, such as ornaments, colors, typography, and national symbols. Results. The study proposed a typology of logos with ethnic elements: textbased (typographic stylizations), graphic (with ornamental motifs), emblematic (with state symbols), and hybrid. In particular, it examined logos of brands such as CHERNIKOVA, ZARINA, Kalyna Store, Dukach, Zerno, Varenyky Fashion, as well as state institutions DART and the Faculty of Prosecution of the Yaroslav Mudryi National Law University. The analysis emphasized the harmonious combination of ethnic codes – such as viburnum clusters, stars, rhombuses, and the trident – with contemporary graphic language. It also described color solutions (for example, redblack and blue-yellow combinations) that enhance the emotional impact and cultural authenticity of the logos. Scientific novelty. A systematic analysis of ethno-design in logos was carried out within a cultural-communicative paradigm. The study deepens the understanding of ethno-design as a means of visual representation of national identity and cultural memory within brand communication. Practical relevance. The results of the study can be used in graphic design practice, branding, cultural management, visual communications, and educational programs in the fields of design, art history, and cultural studies. The presented conclusions can serve as a foundation for further research on Ukrainian visual culture in the context of digital transformation.